The ultimate ambition in the arts of erudition a compendium of knowledge from the classical Islamic world - Nuwayrī, Aḥmad ibn ʻAbd al-Wahhāb 1279-1333 (Penguin classics, 2016)
An astonishing record of the knowledge of a civilization, The Ultimate Ambition in the Arts of Erudition catalogs everything known to exist from the perspective of a fourteenth-century Egyptian scholar and litterateur. More than 9,000 pages and thirty volumes-here abridged to one volume, and translated into English for the first time-it contains entries on everything from medieval moon-worshipping cults, sexual aphrodisiacs, and the substance of clouds, to how to get the smell of alcohol off one's breath, the deliciousness of cheese made from buffalo milk, and the nesting habits of flamingos.